Analisis Dalam Pendukung Keputusan Seleksi Reporter dengan Menerapkan Metode EDAS dan Pembobotan ROC - Pitrasacha Adytia; Muhammad Fahmi; Reza Andrea (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
The community's need for curiosity about the latest information makes news something that is always sought after and never goes extinct. One of the important elements in the world of news is the reporter. Reporters are people who are involved or play an important role in finding the latest information and covering everything that happens and conveying news or facts that happened at the scene directly to the public. In addition, reporters are also tasked with compiling various important information in a systematic and easy-to-understand manner so that the public can understand well about whatever is conveyed by the reporter. However, the amount of data makes it difficult for companies to select potential reporters. Because if done manually it is less effective. To solve these problems, a decision support system was created to assist the company in determining which applicants should be accepted. A decision support system (DSS) is a system that was created with the aim of helping parties who have difficulty making a decision or making an election with large amounts of data. In this study the method used is the EDAS method. the EDAS method is a method that functions to produce a ranking value from several choices so that a calculated value is obtained from each criterion attribute value. Based on the results of the research that has been carried out and has been carried out regarding the selection of prospective reporters who are eligible to be accepted by companies by optimizing the Decision Support System function by implementing the EDAS (Evaluation Based On Distance From Average Solution) method and the Rank Oder Centroid (ROC) weighting method, it is obtained the result is equal to 1.3093 with code B4 on behalf of syahputra as a reporter candidate that the company deserves to accept.